Greek tragedy on the move : the birth of a Panhellenic art form c. 500-300 BC - Stewart, Edmund (Oxford University Press, 2017)
What made Greek tragedy 'Greek'? Tragic theatre is often seen primarily as a cultural product of one city: Athens. By contrast, this volume argues that it was a panhellenic phenomenon, born out of travel in the fifth century BC, in which audiences, poets, actors, and the heroes they played were continually on the move across the Greek world